Investigation of a polymer-based SAW sensor to detect volatile organic compound (VOC) - Mohamad Sabri, Nur Fatin Nabilah; Za'bah, Nor Farahidah; Md Ralib @ Md Raghib, Aliza 'Aini (AlamBiblio Publishers, 2023)
Two surface acoustic wave (SAW) sensors with polyethyleneimine (PEI) and polyisobutylene (PIB) layers respectively are modelled by using COMSOL Multiphysics software to detect acetone, benzene, and toluene. The main parameter of the SAW sensor is the thickness of the sensing layer, and the concentration of VOCs is varied to study their relationships with regard to the sensitivity of the SAW sensor. Both configurations portrayed the same pattern where the frequency shift and the sensitivity increase as the concentration of VOCs increases. In addition, the two layers have also produced promising results in sensing toluene even as low as 5 ppm which means that both layers are more selective towards toluene when the three VOCs are concurrently presented on the surface of the sensor. The data also shows that in detecting acetone and benzene, the PEI layer showed higher shifts in frequencies as compared to the PIB layer.